Acceleration of Government Administration Services at Government Bureu and Border Regional Secretariat of the Riau Island Province through the Implementation of E-Government - Kurniawan, Kurniawan; Ikhsan, M; Yuliana, Ernik (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2024)
The Government and Border Bureau of the Regional Secretariat of the Riau Islands Province faces the problem of government services that are not yet optimal due to the weakness of the government administration service system. These weaknesses include the fact that manual systems are still used, which are not updated and are not responsive to regional conditions, changes, and technological developments. For this reason, it is necessary to accelerate services through the implementation of e-government. Starting from these problems, the aim of this research is to analyze the acceleration of government administration services at the Government and Border Bureau of the Regional Secretariat of Riau Islands Province through the implementation of e-government. This research is a qualitative descriptive study. This research was conducted on employees of the Government and Border Bureau of the Regional Secretariat of Riau Islands Province and obtained by conducting in-depth interviews with selected informants. Data analysis was carried out descriptively. The research concludes that the acceleration of government administration services carried out at the Government and Border Bureau of the Regional Secretariat of the Riau Islands Province through the implementation of e-government has gone well and can provide services that are easier, faster, and more open, thus making it easier for applicants.